Circumcision and periurethral carriage of Proteus mirabilis in boys. Issue 5 (May 1988) - Glennon, J; Ryan, P J; Keane, C T; Rees, J P
Abstract : Swabs were taken for culture from the periurethral area and urethral meatus in 124 uncircumcised and 60 circumcised boys. Proteus mirabilis was grown from 28 (22.6%) swabs from uncircumcised boys and from only one (1.7%) swab from circumcised boys. This supports the idea that the prepuce may be the source of proteus urinary tract infection.